Whole‐Mount Preparation and Microscopic Analysis of Epidermis. Issue 7 (11th July 2022) - Kubo, Akiharu; Aoki, Satomi; Fujita, Harumi
Abstract: The epidermis is a stratified epithelium. Compared to that for monolayered epithelia, understanding of the cell biology of stratified epithelia lags far behind. The major reason for this is the limitation of methods to reproduce the epidermis in vitro using cultured keratinocytes: for example, cultured keratinocyte cell sheets lack Langerhans cells, melanocytes, nerves, sweat ducts, and hair follicles. One current way to overcome this limitation is to observe the epidermis in vivo via whole‐mount staining and three‐dimensional imaging. Here, we describe how to prepare epidermal sheets from skin and how to immunostain and observe them in whole mount. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of mouse epidermal sheets by the ammonium thiocyanate method Alternate Protocol : Preparation of mouse epidermal sheets by the dispase method Basic Protocol 2 : Preparation of human epidermal sheets by the dispase method Basic Protocol 3 : Whole‐mount immunostaining of epidermis